Death kinetics of Escherichia coli in goat milk and Bacillus licheniformis in cloudberry jam treated by ohmic heating - Pereira, Ricardo (2006)
In recent years, the world’s food industry has focused increasing attention on electrical techniques of food processing. Ohmic heating is one of these techniques that can be considered as a high temperature short time and a purely bulk heating method, having potential applications in processes such as blanching, evaporation and pasteurization in the food industry. However such technology would have to assure the microbiological safety obtained by the conventional cooking methods. Concerning this, the influence of heat treatment by ohmic and conventional technology on death kinetic parameters (D and z values) of Escherichia coli ATCC® 25922 was studied in goat milk. In ohmic treatment lower D values were obtained (D60ºC = 4.2 min, D63ºC = 1.9 min, D65ºC = 0.86 min) as compared to conventional treatment (D63ºC = 3.9 min, D65ºC = 3.5, D67ºC = 2.8 min, D75ºC = 1.5 min). The increase of temperature required for a ten fold decrease in D value was also lower in the ohmic inactivation (z = 8.4 ºC) comparing with the conventional inactivation (z = 23.1 ºC). The death kinetics for Bacillus licheniformis ATCC® 14580 spores in cloudberry jam were also studied under both types of heat inactivation (ohmic and conventional) and similar conclusions were drawn for the D values; lower D values were also obtained for ohmic treatment (D70ºC = 57.1 min, D75ºC = 25.2 min, D80ºC = 7.2 min) as compared to conventional treatment (D70ºC = 85.3 min, D75ºC = 51.0, D80ºC = 18.1 min, D85ºC = 6.0 min, D90ºC = 1.6 min). However, between the z values obtained for those treatments (z ohmic = 11.1 ºC and z conventional = 11.4 ºC) the differences were not significant. In general the results of present work indicate that the ohmic heating provides quicker death kinetics. This opens the perspective for shorter, less aggressive treatments.